Analisis Daya Saing, Mutu dan Pemasaran Kopi di Desa Karang Lantang Kecamatan Muara Jaya Kabupaten Oku - Putri, Adela Tiara; Pusvita, Ema; Septianita, Septianita (Universitas Galuh, 2024)
The competitiveness of coffee makes coffee quality the main requirement in marketing coffee products. This research aims to analyze the competitiveness, quality and marketing of coffee in Karang Lantang Village, Muara Jaya District, OKU Regency. The research method used is a survey method and data collection using simple random sampling. The number of respondents used in this research was 30 samples. Analysis of coffee competitiveness data uses Police Analysis Matrix (PAM) calculations, quality analysis uses perception questionnaires so that the results are in percentage form, and for marketing it is analyzed using marketing margins. The results of this research are that coffee farmers in Karang Lantang Village, Muara Jaya District, OKU Regency have private profits of Rp. 48,378,333 and social benefits of Rp. 39,518,333. Coffee farmers in Karang Lantang Village, Muara Jaya District, OKU Regency have strong competitiveness because they have comparative advantages and competitive advantages with a DRC value of 0.023 and competitive advantages with a PCR value of 0.021. The results of the quality of coffee in Karang Lantang village, Muara Jaya District, OKU Regency, are the picking process, sorting processing, packaging and warehousing with a number of frequently carried out as many as 342.86 percent and very often carried out as much as 57.14 percent. Coffee farmers in Karang Lantang Village, Muara Jaya District, OKU Regency have haphazard marketing of coffee sales by selling to collectors. Coffee marketing in Karang Lantang Village shows results of around 3.03%. The convenience of a cash economy and no special treatment for the coffee being sold are the main reasons why farmers sell coffee to collectors.